2021
DOI: 10.21203/rs.3.rs-529105/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased risk of chronic fatigue and hair loss following COVID-19 in individuals with hypohidrotic ectodermal dysplasia

Abstract: Background Hypohidrotic ectodermal dysplasia (HED) is a group of genodermatoses in which deficient ectodysplasin A signalling leads to maldevelopment of skin appendages, various eccrine glands, and teeth. Individuals with HED often have disrupted epithelial barriers and, therefore, were suspected to be more susceptible to coronavirus infection. Methods 56 households with at least one member who had coronavirus disease of 2019 (COVID-19) were enrolled in a longitudinal study to compare the course of illness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A rigorous meta-analysis of several studies found that after COVID-19, 80% of the population, aged 17 to 87, had long-lasting effects. Because COVID-19 infections in children are less common and their symptoms are milder than those in adults with COVID-19, the majority of cases of hair loss occur in adults (33).…”
Section: Evaluating the Role Of Thyroid Stimulating Hormone And Ferri...mentioning
confidence: 99%
“…A rigorous meta-analysis of several studies found that after COVID-19, 80% of the population, aged 17 to 87, had long-lasting effects. Because COVID-19 infections in children are less common and their symptoms are milder than those in adults with COVID-19, the majority of cases of hair loss occur in adults (33).…”
Section: Evaluating the Role Of Thyroid Stimulating Hormone And Ferri...mentioning
confidence: 99%